2018
DOI: 10.1088/1367-2630/aadbc3
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing local information transfer in Boolean networks

Abstract: We study a Boolean network model such that rules governing the time evolution of states are not given a priori but emerge from the maximization process of local information transfer and are stabilized if possible. We mathematically derive the class of rules that can be stabilized. With the presence of small noise, those stabilized are such that their output depends on a unique input. We confirm the prediction of the theory by numerical simulation. We argue that the stabilized rules have generic properties of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…However we phrase it, the idea is that information processing, responsiveness, and problem-solving capacity are optimal when a system is on the edge of instability, near a critical state [149][150][151]. Moreover, long-range correlations (e.g., cooperation between distant, non-neighboring parts) increase near criticality [145].…”
Section: Self-organized Criticalitymentioning
confidence: 99%
“…However we phrase it, the idea is that information processing, responsiveness, and problem-solving capacity are optimal when a system is on the edge of instability, near a critical state [149][150][151]. Moreover, long-range correlations (e.g., cooperation between distant, non-neighboring parts) increase near criticality [145].…”
Section: Self-organized Criticalitymentioning
confidence: 99%
“…One of these dual dynamics is the dynamics of states forming cellular automata, and the other is the dynamics of the LTE. We previously proposed a similar model system based on a Boolean network that maximizes the local mutual information between interacting agents, and we showed that its time evolution rule always degenerates into a critical and highly canalized rule [25]. The major differences between our current model and the previous one are the introduction of space (interacting with the neighborhood) and the use of LTE.…”
Section: Cellular Information Transfer (Cit) System: Formalizations Amentioning
confidence: 97%
“…However we phrase it, the idea is that information processing, responsiveness, and problem-solving capacity are optimal when a system is on the edge of instability, near a critical state [151][152][153]. Moreover, long-range correlations (e.g., cooperation between distant, non-neighboring parts) increase near criticality [147].…”
Section: Self-organized Criticalitymentioning
confidence: 99%